Application of Mastic Asphalt Using Rubber Added Modified Bitumen - ALUÇ, Salih; AHISKALI, Adem (Kirsehir Ahi Evran University, 2023)
Transportation is the movement of people and goods from one place to another place. Besides there are many transportation systems in our country, road transportation has the most important place and has a share of 95 percent. Highways are structures that are built flexibly and rigidly on the ground floor and allow fast, safe and comfortable passage of vehicles. A road network that has an orderly distribution has become an important element in the development of countries. Because a strong and comfortable road network provides easy access to energy resources, fast and timely delivery of the products produced and saving time. Today, it is obvious that many studies need to be done in bitumen by adding various additives to bitumen in order to make the roads built more comfortable and durable. While polymer modification is now being applied effectively, it comes up to the agenda that it will provide better compaction and economic contributions by increasing the processability properties. Thanks to such additives, the workability feature can contribute to performance. In this study, different proportions of rubber additives, modified bitumen and mastic asphalt applications were discussed. Today, SMA (Stone, Mastic, Asphalt) layer is used as a high quality wear layer. SMA layers, which are generally obtained from mixtures of 70 - 80% coarse aggregate, 20 - 30% fine aggregate and 6 - 8% asphalt type (high amount of space between aggregates) stands out due to its features such as being more resistant to permanent damage and abrasion, higher quality and being more homogeneous and impermeable. any project success is defined by techniques improved quantity to facilitate effective cost control, cost and time estimation.
Keywords: Engineering; Mastik asfalt; Mekanik özellikler; Kauçuk katkılı; Modifiye bitüm; Kauçuk modifiye asfalt; Asfalt karışımı.; Mühendislik; Mastic asphalt; Mechanical properties; Rubber added; Modified bitumen; Rubber modified asphalt; Asphalt codes; 13. Climate action; 11. Sustainability; 7. Clean energy; 12. Responsible consumption